From Shock to Awe: The Awe of Organisation: How do Community-Based Festivals do Institutional Work? - Turner, Fergus (Graduate School of Business (GSB), 2021)
This thesis is based on an action research project with festival organisations and festival organising and is interested in key insights and practice models for changing meaning-making, routines, roles and resource flows and effectively doing what scholars of institutional theory call institutional work. The project is located in a central case study, the Muizenberg Festival, where I haved played a role as a coordinator, and have co-designed the festival process and platform between 2014 and 2019. It is further bolstered by research with several social-purpose festivals, from local and international case studies. The present socio-economic development discourse and practice prevalent in South Africa, and the developing South more generally, has been bounded and constrained by strategies that fail to address a milieu of institutionalised issues. If people cannot exercise agency on underlying institutionalised issues, alternative vehicles for organising in order to do such work are necessary. Festivals exhibit large-scale participation around specific themes in a concentrated time frame. Festivals are known to produce an array of social and economic goods including, amongst others, sense of community and social capital. This study will explore new theoretical perspectives on organisations and institutional work through action research with community-based social-purpose festivals. The study aims to provide cogent theoretical and practical frameworks for the study and practice of festivals as organisations and social phenomena that are pertinent to the study of institutional work, offering a model of development with important learnings for addressing intractable socio-economic issues in innovative ways. The research is embedded with the backdrop of literature that specifically looks at, however not exclusively, institutional theory and festival studies. Three years of action research data, in the form of observation, dialogue interviews, working journals, meeting notes and reports will be used spanning from 2015 until 2017. From this learning, the case will be made for festival organising models as offering new insights for transformative development and provide strategies for deploying tactics of community-based festivals as compelling new approaches to institutional work, from the ground up.